Neurological diseases of cattle diagnosed by histopathology in Minas Gerais: cattle - Oliveira, Taismara S.; Bull, Valquíria; Furtini, Ronaldo; Drummnond, Safira R. M.; Costa, Érica A.; Santos, Renato L.; Paixão, Tatiane A. (Brazilian Journal of Veterinary Pathology, 2016)
This study was based on analysis of the central nervous system from cattle that died after developing neurological disease in the State of Minas Gerais from 2004 to 2010. Samples were analyzed by histopathology, histochemistry, and anti-Listeria monocytogenes immunohistochemistry. The frequency of positivity for the techniques used and distribution were determined, and the results were analyzed by Fisher's exact test. Microscopic changes were observed in 29.5% (290/982) of bovine central nervous system samples examined. Inflammatory changes were the most frequent lesions (87.2% - 253/290) with 80% of cases (232/290) presenting non suppurative inflammation. Through histopathologic analyses, presumptive or conclusive etiology was obtained in 25.2% (73/290) of the samples. Etiologic diagnosis included inflammation by viruses (bovine herpesvirus infection in six samples; ovine herpesvirus-2 infection in eight samples); and bacteria (bacterial infection in 34 samples; and tuberculosis in six samples). Circulatory changes were evident in 26 cattle being nine cases of cerebral babesiosis. Degenerative lesions were detected in eight samples. One congenital change (cerebellar abiotrophy) and one neoplasm (astrocytoma) were identified. Neurological diseases other than rabies were diagnosed in Minas Gerais, and the use of histopathology allowed a more accurate differential diagnosis and a higher rate of conclusive diagnoses.